Sex-related differences in postoperative complications following elective craniotomy for intracranial lesions: An observational study. Issue 27 (8th July 2022) - Brandi, Giovanna; Stumpo, Vittorio; Gilone, Marco; Tosic, Lazar; Sarnthein, Johannes; Staartjes, Victor E.; Wang, Sophie Shih-Yüng; Van Niftrik, Bas; Regli, Luca; Keller, Emanuela; Serra, Carlo
Abstract : Introduction: The integration of sex-related differences in neurosurgery is crucial for new, possible sex-specific, therapeutic approaches. In neurosurgical emergencies, such as traumatic brain injury and aneurysmal subarachnoid hemorrhage, these differences have been investigated. So far, little is known concerning the impact of sex on frequency of postoperative complications after elective craniotomy. This study investigates whether sex-related differences exist in frequency of postoperative complications in patients who underwent elective craniotomy for intracranial lesion. Material and Methods: All consecutive patients who underwent an elective intracranial procedure over a 2-year period at our center were eligible for inclusion in this retrospective study. Demographic data, comorbidities, frequency of postoperative complications at 24 hours following surgery and at discharge, and hospital length of stay were compared among females and males. Results: Overall, 664 patients were considered for the analysis. Of those, 339 (50.2%) were females. Demographic data were comparable among females and males. More females than males suffered from allergic, muscular, and rheumatic disorders. No differences in frequency of postoperative complications at 24 hours after surgery and at discharge were observed among females and males. Similarly, the hospital length of stay was comparable. Conclusions: In the present study, no sex-related differences in frequency of early postoperative complications and at discharge following elective craniotomy for intracranial lesions were observed.